FAMILY CERATOPOGONIDAE - Spinelli, Gustavo A.; Wolff, Marta (Zootaxa, 2016)
Two hundred and thirty five species of Ceratopogonids arranged in 28 genera are listed for Colombia, mostly Culicoides (112 species) and Forcipomyia (50 species). For each listed species, information on type locality, type category and sex, location of type material, species distribution, localities for Colombia and main references, is provided. Localities are not specified for 17 species in which the literature searching was negative. Forcipomyia squamitibia Lutz and Bezzia clavipennis are excluded from the list.